Modelling and simulation of electric drive vehicle based on Space Vector Modulation technique and Field Oriented Control strategy - Fadul S.M.E.; Aris I.; Misron N.; Halin I.A.; Iqbal A.K.M.P. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric drives; Electric machine control; Electric vehicles; Energy conservation; Energy efficiency; Energy policy; Frequency modulation; Induction motors; Internal combustion engines; MATLAB; Modulation; Pulse width modulation; Traction motors; Vector spaces; Vehicles; Electric vehicle drive; Electric-drive vehicles; Environmental pollutions; Induction motor efficiency; Modelling and simulations; Space Vector Modulation; Transportation sector; Vehicle dynamics; Vector control (Electric machinery)